A Rare Case of Lower Limb Poroid Hidradenoma - Anggreana, Farisa; Shelly, Wan Gifanni Efmadian; Fitriani, Katia; Andayani, Raden Roro Rini; Wirohadidjojo, Yohanes Widodo (http://dharmais.co.id/, 2025)
Introduction: Poroid hidradenoma (PH) is a benign tumor of the eccrine gland, which is the rarest variant of poroid tumor. The case reports that have been published since 1990 are around 75 cases. The presentation of PH lesions is nonspecific and varied, which often leads to misdiagnosis and requires histopathological examination to confirm the diagnosis. Case Presentation: A 53-year-old woman came with complaints of a prominent wound on her right lower leg for 4 years. Physical examination showed a partially bluish erythematous nodule accompanied by blackish brown crusted erosion in the central area, 1 cm in diameter, and solitary. Dermoscopic examination shows a central blue-grey pigmented area, a whitish halo, and erosion. The differential diagnosis of this case is keratoacanthoma, eccrine poroma, dermal duct tumor, and PH. Histopathological findings showed solid and cystic components, as well as poroid and cuticular cells in the dermis area. The final diagnosis in this case is PH.Conclusion: This report shows the challenge of PH diagnosis that requires an in-depth understanding of the clinical manifestation, dermoscopic, and histopathologic features.